A Case of Acute Motor Axonal Neuropathy Mimicking Brain Death and Review of the Literature - Ravikumar, Sandhya; Poysophon, Poysophon; Poblete, Roy; Kim-Tenser, May (Frontiers in Neurology, 2016)
We describe a case report of fulminant Guillain-Barré syndrome mimicking brain death. A previously healthy 60-year-old male was admitted to the neurointensive care unit after developing rapidly progressive weakness and respiratory failure. On presentation, the patient was found to have absent brainstem and spinal cord reflexes resembling that of brain death. Acute motor axonal neuropathy (AMAN), a subtype of Guillain-Barré syndrome, was diagnosed by cerebrospinal fluid and nerve conduction velocity testing. An electroencephalogram showed that the patient had normal, appropriately reactive brain function. Transcranial Doppler ultrasound showed appropriate blood flow to the brain. Guillain-Barré syndrome rarely presents with weakness so severe as to mimic brain death. This article provides a review of similar literature. This case demonstrates the importance of performing a proper brain death examination, which includes evaluation for irreversible cerebral injury, exclusion of any confounding conditions, and performance of tests such as electroencephalography and transcranial dopplers when uncertainty exists about the reliability of the clinical exam.